Formal Assumptions and Limitations of Circular Models in Typologizing Psychological and Educational Theories - Agnieszka Szymańska (Studia z Teorii Wychowania, 2025)
This article discusses the limitations of circular models in psychology and pedagogy, which stem from their inherent reliance on the trigonometric properties of angles and distances in two-dimensional space. Circular models, despite being a popular tool for visualizing and classifying psychological and educational types, encounter problems with accuracy and reliability as the number of dimensions analyzed increases.In response to these challenges, the article introduces spherical models, which by adding a third dimension offer the possibility of better representing complex psychological structures. Additionally, the use of Support Vector Machines (SVM) with a Radial Basis Function (RBF) kernel has been proposed as a method capable of more effective analysis and verification of spherical models.SVM with an RBF kernel enables data transformation into a multidimensional space, allowing for more precise modeling and classification of complex patterns. The article emphasizes the need for the development of new analytical tools that could address the specific challenges associated with spherical models, as well as future possibilities for their application in psychological and educational research.The discussion also includes a review of verification methods and potential development directions in the context of theory and practice.